Novel Genes and Genetic Loci Associated With Root Morphological Traits, Phosphorus-Acquisition Efficiency and Phosphorus-Use Efficiency in Chickpea - Thudi, Mahendar; Chen, Yinglong; Pang, Jiayin; Kalavikatte, Danamma; Bajaj, Prasad; Roorkiwal, Manish; Chitikineni, Annapurna; Ryan, Megan H.; Lambers, Hans; Siddique, Kadambot H. M.; Varshney, Rajeev K. (Frontiers in Plant Science, 2021)
Chickpea—the second most important grain legume worldwide—is cultivated mainly on marginal soils. Phosphorus (P) deficiency often restricts chickpea yields. Understanding the genetics of traits encoding P-acquisition efficiency and P-use efficiency will help develop strategies to reduce P-fertilizer application. A We used genomeGgenome-wide association mapping approach was used to determine loci and genes associated with root architecture, root traits associated with P-acquisition efficiency and P-use efficiency, and any associated proxy traits. We usedUsing three statistical models—a generalized linear model (GLM), a mixed linear model (MLM), and a fixed and random model circulating probability unification (FarmCPU) —to identify 10, 51, and 40 marker-trait associations (MTAs), respectively were identified. We identified Aa single nucleotide polymorphism (SNP) locus (Ca1_12310101) on Ca1 associated with three traits, i.e. physiological P-use efficiency, shoot dry weight, and shoot P content was identified. GWe also identified several genes related to shoot P concentration (NAD kinase 2, dynamin-related protein 1C), physiological P-use efficiency (fasciclin-like arabinogalactan protein), specific root length (4-coumarate--CoA ligase 1) and manganese concentration in mature leaves (ABC1 family protein) were identified. The MTAs and novel genes identified in this study can be used to improve P-use efficiency in chickpea.